Chitooligosaccharides enhance cold tolerance by repairing photodamaged PS II in rice. (26th October 2018) - Zhou, Jiachun; Chen, Qiao; Zhang, Yang; Fan, Liqiang; Qin, Zhen; Chen, Qiming; Qiu, Yongjun; Jiang, Lihua; Zhao, Liming
Abstract: Chitooligosaccharides (COS) are multi-functional foods and nutrients and environmentally friendly biological abiotic-resistance inducing agents for plants. In the current study, the effects and possible mechanisms of COS on improving the cold resistance of rice (II YOU 1259) seedlings were investigated. Compared with the control, a COS pre-soaking treatment enhanced photosynthesis, reduced oxidation damage and led to accumulation of more osmotic regulation substances under chilling treatment. In addition, a novel Deg/HtrA family serine endopeptidase (DegQ) gene, related to COS enhanced rice cold resistance, was identified. Quantitative real-time polymerase chain reaction (qRT-PCR) analysis revealed that transcription of DegQ and psbA (D1 protein encoding gene) were up-regulated in a time-dependent manner by COS treatment under cold stress. With increasing expression of the D1 protein, chlorophyll b content was enhanced correspondingly. The current results suggest that COS could enhance cold stress tolerance of rice by repairing the photodamaged photosystem II, altering osmotic regulation and reducing oxidation damage.